Nursing management of bleeding after transurethral resection of the prostate in a patient with maintenance hemodialysis (1例维持性血液透析患者经尿道前列腺电切术后出血的护理体会) - LIN Yuqing (林玉卿); YU Fengyun (余烽云) (Association of Integrative Nursing, 2022)
This paper summarized the nursing management of bleeding after transurethral resection of the prostate in a patient with maintenance hemodialysis. Key issues including monitoring the patient's vital signs; accurately recording and controling the patient's flow of water in and out; paying attention to the color, quality and quantity of the urine; monitoring the patient's blood routine test, renal function and electrolytes; strengthening the nutrition support; strengthening early rehabilitation treatment; carrying out the early psychological intervention; relieving patient's anxiety and other adverse emotions. (本文总结1例维持性血液透析患者行经尿道前列腺电切术(TURP)术后出血的护理经验。护理要点包括: 监测患者生命体征, 准确记录并控制患者的出入水量; 关注患者尿液的色、质、量; 监测患者的血常规、肾功能及电解质; 加强营养; 加强早期康复治疗; 贯彻落实早期心理干预, 缓解患者焦虑等不良情绪。)